Characterizing and Diminishing Autofluorescence in Formalin-fixed Paraffin-embedded Human Respiratory Tissue. (June 2014) - Davis, A. Sally; Richter, Anke; Becker, Steven; Moyer, Jenna E.; Sandouk, Aline; Skinner, Jeff; Taubenberger, Jeffery K.
Tissue autofluorescence frequently hampers visualization of immunofluorescent markers in formalin-fixed paraffin-embedded respiratory tissues. We assessed nine treatments reported to have efficacy in reducing autofluorescence in other tissue types. The three most efficacious were Eriochrome black T, Sudan black B and sodium borohydride, as measured using white light laser confocal Λ 2 (multi-lambda) analysis. We also assessed the impact of steam antigen retrieval and serum application on human tracheal tissue autofluorescence. Functionally fitting this Λ 2 data to 2-dimensional Gaussian surfaces revealed that steam antigen retrieval and serum application contribute minimally to autofluorescence and that the three treatments are disparately efficacious. Together, these studies provide a set of guidelines for diminishing autofluorescence in formalin-fixed paraffin-embedded human respiratory tissue. Additionally, these characterization techniques are transferable to similar questions in other tissue types, as demonstrated on frozen human liver tissue and paraffin-embedded mouse lung tissue fixed in different fixatives.